2000
DOI: 10.1093/carcin/21.12.2219
|View full text |Cite
|
Sign up to set email alerts
|

XPD/ERCC2 polymorphisms and risk of head and neck cancer: a case-control analysis

Abstract: DNA repair capacity is central in maintaining normal cellular functions. Variants of several DNA repair genes,including the nucleotide excision repair gene XPD, have been described recently. Because we previously reported that patients with squamous cell carcinoma of the head and neck (SCCHN) had lower DNA repair capacity than healthy controls, we hypothesized that inherited polymorphisms of XPD may contribute to genetic susceptibility to SCCHN, a tobacco-related cancer. To test this hypothesis, we conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
97
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 10 publications
14
97
0
1
Order By: Relevance
“…The A > C (Arg > Arg) polymorphism at codon 156 of XPD was screened in all samples generating a 644-bp PCR product, digesting with TfiI and electrophoresing in 2% agarose gel. 14 In addition to the TfiI site at codon 156, one additional monomorphic TfiI site, producing a 57-bp DNA fragment, served as an internal control for restriction enzyme digestion. Genotypes were determined by banding patterns such as A/A (474, 113 and 57 bp); A/C (587, 474, 113 and 57 bp); and C/C (587, 57 bp).…”
Section: Sample Collection and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The A > C (Arg > Arg) polymorphism at codon 156 of XPD was screened in all samples generating a 644-bp PCR product, digesting with TfiI and electrophoresing in 2% agarose gel. 14 In addition to the TfiI site at codon 156, one additional monomorphic TfiI site, producing a 57-bp DNA fragment, served as an internal control for restriction enzyme digestion. Genotypes were determined by banding patterns such as A/A (474, 113 and 57 bp); A/C (587, 474, 113 and 57 bp); and C/C (587, 57 bp).…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…Several synonymous and nonsynonymous SNPs including those at codons 156 (exon 6 C > A, Arg > Arg), 312 (exon 10 G > A, Asp > Asn) and 751 (exon 23 A > C, Lys > Gln) have been described in XPD locus and reported to be associated with tobacco related cancers. 14,15 The XRCC1 plays an important role in base excision repair (BER) pathway, and interacts with DNA polymerase b, poly ADP-ribose polymerase and DNA ligase III. It also contains a BRCT (BRCA1 COOH terminus) domain, which is characteristic of proteins involved in cell cycle checkpoint functions and this domain can be responsive to DNA damage.…”
mentioning
confidence: 99%
“…8 Briefly, patients with newly diagnosed and histologically confirmed SCCHN (i.e., having primary tumors of the oral cavity, pharynx and larynx) were recruited from May 1995 to November 2001 at the Department of Head and Neck Surgery of M.D. Anderson Cancer Center.…”
Section: Study Subjectsmentioning
confidence: 99%
“…5,6 Recent molecular epidemiological studies have demonstrated that polymorphisms in DNA repair genes contribute to genetic susceptibility to SCCHN. 7,8 Therefore, studies of biological relevance of newly identified genetic polymorphisms 9 should ultimately help identify those at high risk for carcinogenesis and eventually improve cancer prevention and chemoprevention programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation